Wiley Encyclopedia of Electrical and Electronics Engineering 2014
DOI: 10.1002/047134608x.w8206
|View full text |Cite
|
Sign up to set email alerts
|

Peltier Effect in Semiconductors

Abstract: In recent years, devices based on the Peltier effect, which is the basis for solid‐state thermoelectric cooling, have evolved rapidly to meet the fast‐growing electronic industry. The Peltier effect corresponds to the heat extraction or absorption occurring at the contact between two different conducting media when a direct current (DC) electric current flows through this contact. A comprehensive study of the mechanisms of heating and cooling originated by an electrical current in semiconductor devices is repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…In 1834, Jean Charles Athanase Peltier, a French physicist, discovered the presence of heat at an electrified junction between two different conductors, namely, the Peltier effect. Since then, the aspects of the nonequilibrium thermodynamics of thermoelectric phenomena related to the Peltier effect in a semiconductor have received special attention [12]. One of the results archived when studying the Peltier effect in a quantum wire showed that a quasi-equilibrium situation is reached a defined local temperatures [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 1834, Jean Charles Athanase Peltier, a French physicist, discovered the presence of heat at an electrified junction between two different conductors, namely, the Peltier effect. Since then, the aspects of the nonequilibrium thermodynamics of thermoelectric phenomena related to the Peltier effect in a semiconductor have received special attention [12]. One of the results archived when studying the Peltier effect in a quantum wire showed that a quasi-equilibrium situation is reached a defined local temperatures [13].…”
Section: Introductionmentioning
confidence: 99%
“…The sensor comprises an actively controlled thermistor inside the mask along with a Thermoelectric Cooler (TEC) outside the mask. The device maintains the thermistor in thermal balance with the TEC utilizing the Peltier effect . During power‐up initialization, the sensor measures the ambient temperature and uses this as a set point for the control loop.…”
Section: Methodsmentioning
confidence: 99%
“…The device maintains the thermistor in thermal balance with the TEC utilizing the Peltier effect. 17,18 During power-up initialization, the sensor measures the ambient temperature and uses this as a set point for the control loop. As the expired breath heats the thermistor, the thermal balance is disrupted and this generates a feedback signal via the control loop.…”
Section: Device Descriptionmentioning
confidence: 99%
“…Following a similar approach described earlier, expressions can be derived for . For example, for the ND and D cases, the Peltier coefficient takes the following forms [22]:…”
Section: Basic Thermoelectric Phenomena and Materials Physicsmentioning
confidence: 99%